“Caracterización morfológica de la colección de aguacate (Persea americana) de la Estación Experimental Tropical - Pichilingue. (EETP)” - Acurio Albiño, Joshua Alexander (2022)
The avocado plant (Persea americana) is a tree from the angiosperm group. Currently, the economic growth of avocado is in force for its food use. The morphological description of the avocado allows knowing the desired variables in phytogenetic studies to increase production and reduce diseases. From this context, the following research study has as its purpose a morphological characterization of the avocado (Persea americana) from the accessions of the EET - Pichilingue research center. For the following work, an observational, descriptive and inductive study was applied Qualitative and quantitative data were characterized using a binary matrix, where the following activities were carried out: determination of genetic variability, discriminant analysis of characters, similarity and distance matrix (Euclidea), taxonomic structure and phenogram using Ward's algorithm. The statistical program INFOSTAT 2020e was used. Among the results, the analysis of the characteristics that presented a greater genetic variability are: the number of flowers per inflorescence (47.75%) and seed weight (29.58%). The discriminant value for quantitative variable with the highest value corresponds to the leaf blade length of group 4 with 28.06 cm and within the qualitative variable, seed shape. In the phonogram, the groupings between the (Persea americana) accessions show the relationship of the similarity between the 4 groups obtained from the accessions with a cophenetic coefficient of 0.92. It is concluded that the quantitative variables with the highest discriminant value were: leaf blade width, leaf blade length and seed diameter and qualitative variables the discriminant values were: seed shape, tree, fruit and leaf. Fruit pulp was found to be a desirable trait for breeding programs.